2015
DOI: 10.1038/srep18070
|View full text |Cite
|
Sign up to set email alerts
|

A combined system of microbial fuel cell and intermittently aerated biological filter for energy self-sufficient wastewater treatment

Abstract: Energy self-sufficiency is a highly desirable goal of sustainable wastewater treatment. Herein, a combined system of a microbial fuel cell and an intermittently aerated biological filter (MFC-IABF) was designed and operated in an energy self-sufficient manner. The system was fed with synthetic wastewater (COD = 1000 mg L−1) in continuous mode for more than 3 months at room temperature (~25 °C). Voltage output was increased to 5 ± 0.4 V using a capacitor-based circuit. The MFC produced electricity to power the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Recent studies have demonstrated modular pilot scale MFCs are capable of being self-sufficient in terms of energy (Dong et al, 2015a;Dong et al, 2015b;Ge & He, 2016), so it is not difficult to imagine a larger MFC being built and tested in the near future. A logical next step would be to test the performance and feasibility of multiple "full-size", modular electrode assemblies (anode, cathode, current collectors and separator, if applicable) that could be directly fitted into a demonstration scale system.…”
Section: Economic Analysismentioning
confidence: 99%
“…Recent studies have demonstrated modular pilot scale MFCs are capable of being self-sufficient in terms of energy (Dong et al, 2015a;Dong et al, 2015b;Ge & He, 2016), so it is not difficult to imagine a larger MFC being built and tested in the near future. A logical next step would be to test the performance and feasibility of multiple "full-size", modular electrode assemblies (anode, cathode, current collectors and separator, if applicable) that could be directly fitted into a demonstration scale system.…”
Section: Economic Analysismentioning
confidence: 99%
“…One way to tackle this challenge is to integrate BESs with other conventional wastewater treatment processes [15,16]. So far, MFCs combined with an anaerobic fluidized bed membrane bioreactor [17] or aerated biological filters [18,19] have been reported. These hybrid reactors are two-stage processes, consist of two separate reactors, and are not integrated as a single reactor.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, MFCs have been studied extensively in the laboratory, but so far only a few on-site pilot-scale (>10 L) bioelectrochemical systems have been built and tested, attaining varying levels of success [5][6][7][8][9][10][11]. Recent pilot studies have demonstrated that MFCs can be self-sufficient [5,7,12], in the sense that the energy captured from the MFCs could be used to power the feed and/or recirculation pump(s).…”
Section: Introductionmentioning
confidence: 99%